PENGGUNAAN MODEL CAPITAL ASSET PRICING MODEL (CAPM) DAN ARBITRAGE PRICING THEORY (APT) DALAM PENGAMBILAN KEPUTUSAN INVESTASI PADA SUB SEKTOR FARMASI DI BURSA EFEK INDONESIA - APRIKA, IIN; SE.M.Si., NURHAYATI OLII (ACCOUNTING STUDY PROGRAM, STIE MUHAMMADIYAH TANJUNG REDEB, 2019)
This study aims to describe the application of the Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) models in making stock investment decisions. This study uses descriptive-quantitative research methods. The data collection technique used is documentation, the data source used is primary data obtained from the Indonesia Stock Exchange (IDX). The object of the study was eight companies in the pharmaceutical sub-sector listed on the Indonesia Stock Exchange. Based on the results of the research that has been done, it shows that of the eight sample companies studied using the Capital Asset Pricing Midel (CAPM) model predicting as many as five companies experiencing Overvalued, three companies experience Undervalued, while the Arbitrage Pricing Theory (APT) model predicts an overall of eight companies get a level of stock returns (Ri) smaller than one. For the accuracy of the two models, there is no difference in the accuracy of the Arbitrage Pricing Theory (APT) model and the Capital Asset Pricing Model (CAPM) model.